Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. The effectiveness of a program based on active learning in developing creative thinking skills among students of the Islamic Studies Curriculum Department at the College of Education, ArhabMs. Samia Ali Ahmed Al-Harazi, Prof. Ahmed Hassan Ghalib, Prof. Hamid Farhan Al-Afif2. The Awareness of Faculty Members and Those in Authority at King Saud University Regarding  the Importance of Reputation Management and Its Impact on Educational InstitutionsMrs. Maha Naif Alotibi, Dr. Saud G. Albeshir3. Organizational culture in school administration in girls’ schools, Asir Education, during the Corona pandemicMs. Norah Khaloofah Hamed4. The Extent of Virtual Reality's Impact on Computer Learning Motivation:  A Comprehensive Review of Literature and Educational ResearchMs. Amirah Mohammed Albalawi5. The level of psychological stress and its relationship to some variables among female students  of the Faculty of Education at the University of HailMrs. Alaa Falah Al-Hamdhawi6. Psychological Hardiness and its relationship to psychological security among female's students  at the University of HailMrs. Sarah Salman Alslemi7. Differences in Emoji Usages Based on Self-Presentation Strategies and Motivations on Social Media and Their Role in Persuasive MessagesMs. Lina Fawaz Alnasrallah, Dr. Heyla Abdullah Alselim8. The degree of awareness of female students exposed to electronic blackmail in the basic stage  of the concepts of moral intelligence and its relationship to the level of blackmailMs. Reema Awwad Alsmeheen, Dr. Anas Saleh Aldalaien
Keywords: Journal of Educational and Psychological Sciences